Identifying Social Issues of Industrial Workers in the Context of Urbanization in Vietnam - Thi Nga, Hoang (VNU Journal of Science: Policy and Management Studies, 2025)
Abstract: The process of urbanization in Vietnam has been accelerating, particularly in the current era of national development. By 2023, the urbanization rate reached 42%. According to the General Statistics Office (2019), there are approximately 6.4 million migrant workers in the country, accounting for 7.3% of the total population. The primary motivation for migration is the pursuit of better economic opportunities, driven by the widening income gap between urban and rural areas. While rapid urbanization has facilitated the development of industrial zones, it has also generated significant social challenges, especially for industrial workers in central urban areas. This paper aims to analyze the workers’ social issues in industrial zones and to propose policy measures to address the challenges faced by employees in urban enterprises. Keywords: Industrial workers, industrial zones, urbanization, new era.